2019
DOI: 10.1002/dc.24252
|View full text |Cite
|
Sign up to set email alerts
|

Utility of endoscopic ultrasound‐guided fine‐needle aspiration cytology in rapid on‐site evaluation for the diagnosis of gastric submucosal tumors: Retrospective analysis of a single‐center experience

Abstract: Background Recently, there have been reports of endoscopic ultrasound‐guided fine‐needle aspiration (EUS‐FNA) cytology being used for the diagnosis of various kinds of tumors. This method has also been adopted in the diagnosis of gastric submucosal tumors (SMTs). The aim of this study was to analyze the utility of EUS‐FNA cytological examination in rapid on‐site evaluation (ROSE) for gastric SMTs. Methods Retrospective analyses of the cytological specimens of EUS‐FNA in ROSE for gastric SMTs and determination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…We observed more tumors were precisely classified on cytology in cases with ROSE as compared to the cases without ROSE (n = 44 vs n = 30, respectively, P < .05) (Table 2). Similarly, Sandoh et al in a study of 120 cases, while evaluating role of ROSE, found 60/62 cases of spindle cell tumor had available cell block material and concluded the importance of ROSE in getting adequate material for preoperative diagnosis 2 . Many of our nondiagnostic cases (9/11, 82%) had cell block material available and was essentially either paucicellular or nonrepresentative.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…We observed more tumors were precisely classified on cytology in cases with ROSE as compared to the cases without ROSE (n = 44 vs n = 30, respectively, P < .05) (Table 2). Similarly, Sandoh et al in a study of 120 cases, while evaluating role of ROSE, found 60/62 cases of spindle cell tumor had available cell block material and concluded the importance of ROSE in getting adequate material for preoperative diagnosis 2 . Many of our nondiagnostic cases (9/11, 82%) had cell block material available and was essentially either paucicellular or nonrepresentative.…”
Section: Discussionmentioning
confidence: 55%
“…With the increasing demand for additional ancillary testing such as identifying mutations for potential benefits of targeted therapy, it is essential to get adequate sample via EUS‐FNA. Rapid onsite evaluation (ROSE) performed at the time of EUS‐FNA procedure has been shown to be a useful method to ensure adequate sampling and triage of the specimen for both diagnostic and further ancillary testing 2 . This study evaluated the role of EUS‐FNA in submucosal and intramural/muscular wall mesenchymal lesions by cytology and histology correlation.…”
Section: Introductionmentioning
confidence: 99%
“…Improvement in the sampling technique and/or method might be required for these patients. The presence of the cytologist at the time of obtaining the cytological specimens and performance of ROSE improved the detection of the targeted lesions in various organs, according to previous studies (11,12). It has been reported that yields of the conventional TBNA with ROSE and EBUS-TBNA with or without ROSE were higher than those of the conventional TBNA without ROSE, although the rates of granuloma detection were not significantly different (7).…”
Section: Discussionmentioning
confidence: 77%
“…Massive studies have already been published regarding the diagnostic yield of EUS-FNAB. 22 - 56 A meta-analysis published in 2016 reports that EUS-guided sampling of upper gastrointestinal subepithelial lesions is safe, but has a moderate diagnostic ability (59.9%) regardless of techniques of FNA/FNB/Tru-Cut needle biopsy or the needle diameter used for puncture. 57 Conversely, a successive meta-analysis reveals that sampling ability of FNA (80.6%) is significantly lower to that of FNB (94.9%), but increase with the help of rapid on-site evaluation.…”
Section: Eus-guided Fine-needle Aspiration/biopsymentioning
confidence: 99%